Size Matters: Spleen and Lung Volumes Predict Performance in Human Apneic Divers - Schagatay, Erika (Frontiers in Physiology, 2012)
Humans share with e.g. seals the ability to contract the spleen and increase circulating hematocrit, which may improve apneic performance by enhancing gas storage. Seals have large spleens and while human spleen size is small in comparison, it shows great individual variation. Unlike many marine mammals, human divers rely to a great extent on lung oxygen stores, but the impact of lung volume on competitive apnea performance has never been determined. We studied if spleen- and lung size correlated with performance in elite apnea divers. Volunteers were 14 male apnea world championship participants, with a mean(SE) of 5.8(1.2) years of previous apnea training. Spleen volume was calculated from spleen length, width and thickness measured via ultrasound during rest, and vital capacity via spirometry. Accumulated competition scores from dives of maximal depth, time and distance were compared to anthropometric measurements and training data. Mean dive performance was 75(4) m for constant weight depth, 5 min 53(39) s for static apnea and 139(13) m for dynamic apnea distance. Subjects’ mean height was 184(2) cm, weight 82(3) kg, vital capacity (VC) 7.3(0.3) L and spleen volume 336(32) ml. Spleen volume did not correlate with subject height or weight, but was positively correlated with competition score (r=0.57; P<0.05). Total competition score was also positively correlated with VC (r=0.54; P<0.05). The three highest scoring divers had the greatest spleen volumes, averaging 538(53) ml, while the three lowest scoring divers had a volume of 270(71) ml (P<0.01). VC was also greater in the high-scorers, at 7.9(0.36) L as compared to 6.7(0.19) L in the low-scorers (P<0.01). Spleen volume was reduced to half after 2 min of apnea in the highest scoring divers, and the estimated resting apnea time gain from the difference between high and low scorers was 15 s for spleen volume and 60 s for VC. We conclude that both spleen- and lung volume predict apnea performance in elite divers.